Password based Smart Doorlock System using Arduino UNO for Enhanced Security - Vinodhini, S.; S, Gnanavarshini; Eby, Sheryl; PA, Divya Prapanjani (IRO Journal on Sustainable Wireless Systems, 2024)
In recent years, the demand for secure access systems has increased significantly, especially in residential and commercial areas. Hence, this presents the design and implementation of a password-based door lock system using an Arduino microcontroller and a servo motor. The system provides a cost-effective and reliable solution for managing access to physical sites. The proposed system uses an Arduino microcontroller as the central device to control the authentication process and to control the servo motor that operates the door locking mechanism. A matrix keyboard is used to enter the password, which provides a user-friendly interface for communication. The servo motor is responsible for physically locking and unlocking the door mechanism based on the authentication result. The operational workflow of the system requires the user to enter a predetermined password using a keyboard. The Arduino microcontroller compares the entered password with the password stored in its memory. After successful authentication, a servo motor is operated to open the door, allowing access to the authorized person. Conversely, failed authentication will result in access being denied.
Keywords: Arduino UNO; 4*4 Keypad lock; Security; Servomotor